Distribution of the pilS gene in Escherichia coli pathovars, its transfer ability and influence in the typical enteropathogenic E. coli adherence phenotype - Garcia, Bruna G.; Castro, Felipe S.; Vieira, Mônica A.M.; Girão, Dennys M.; Uenishi, Lucas T.; Cergole-Novella, Maria C.; dos Santos, Luis F.; Piazza, Roxane M.F.; Hernandes, Rodrigo T. [UNESP]; Gomes, Tânia A.T. (Elsevier, 2019)
Typical enteropathogenic Escherichia coli strains (tEPEC) cause attaching/effacing lesions in eukaryotic cells and produce the bundle-forming pilus (BFP), which interweaves and aggregates bacteria, resulting in the localized adherence (LA) pattern on eukaryotic cells. Previously, we identified tEPEC strains (serotype O119:H6) that exhibited LA simultaneously with an aggregative adherence (AA)-like pattern (LA/AA-like+). Remarkably, AA is characteristically produced by strains of enteroaggregative E. coli (EAEC), another diarrheagenic E. coli pathovar. In one LA/AA-like + strain (Ec404/03), we identified a conjugative plasmid containing the pil operon, which encodes the Pil fimbriae. Moreover, a pil operon associated with an AA pattern and plasmid transfer had been previously described in the EAEC C1096 strain. In this study, we investigated the occurrence of the two pilS alleles (pilSEc404 and pilSC1096) in tEPEC strains of different serotypes, origins and years of isolation. We also examined the potential relationship of pilS with the AA-like phenotype, its ability to be transferred by conjugation, and occurrence among strains of the other E. coli pathovars. The pilS alleles were found in 90 (55.2%) of 163 tEPEC strains, with pilSEc404 occurring more often (30.7%) than pilSC1096 (25.1%). About 21 tEPEC serotypes carried pilS. The pilS alleles were found in tEPEC strains from Chile, Peru and different Brazilian cities, with the oldest strain being isolated in 1966. No absolute correlation was found between the presence of pilS and the AA-like pattern. Conjugative pilS transfer was detected in 26.2% of pilSEc404+ strains and in 65.1% of pilSC1096+ strains, but only pilSEc404+ transconjugants were AA-like+, thus suggesting that the latter allele might need a different genetic background to express this phenotype. pilS was found in all other E. coli pathovars, where it was most prevalent in enterotoxigenic E. coli. More studies are needed to understand the mechanisms involved in the regulation of Pil expression and production.
Keywords: Aggregative adherence; Diarrheagenic E. coli; Enteropathogenic Escherichia coli; Horizontal gene transfer; Pil fimbria; pilS